The The Study of UX on Students’ Perception and Attitude of Using Zoom During Covid-19 Pandemic Using User Centered Design Method - Inacio Campos; Mira Kania Sabariah; Danang Junaedi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The pandemic of COVID-19 resulted in the physical shutdown which has now transformed education into an exclusive